Shock-induced plasticity in nanocrystalline iron: Large-scale molecular dynamics simulations - Luu, Hoang Thien (2020)
Large-scale nonequilibrium molecular dynamics (MD) simulations of shock waves in nanocrystalline iron show evidence of plasticity before the polymorphic transformation takes place. The atomistic structure in the shock direction shows an elastic precursor, plastic deformation, and shock-induced phase transformation from bcc to hcp iron. In this Rapid Communication, large-scale MD models show that the shock response of iron is highly related to the ramp time of the applied shocks. For long ramp times we observe significant plastic relaxation and formation of microstructure defects. Pressure-induced phase transformations in iron are accompanied by stress relaxation achieving almost fully relaxed three-dimensional hydrostatic final states. The evolution of the stress relaxation is in agreement with theory and experiments. Analysis of the x-ray diffraction patterns calculated from the atomistic structure using the Debye equation revealed pronounced anisotropy of the line broadening that is caused by stacking faults in hcp Fe and by dislocations in bcc Fe.